Traumatic Brain Injury-Induced Ependymal Ciliary Loss Decreases Cerebral Spinal Fluid Flow - Xiong, Guoxiang (Mary Ann Liebert, Inc., 2014)
Traumatic brain injury (TBI) afflicts up to 2 million people annually in the United States and is the primary cause of death and disability in young adults and children. Previous TBI studies have focused predominantly on the morphological, biochemical, and functional alterations of gray matter structures, such as the hippocampus. However, little attention has been given to the brain ventricular system, despite the fact that altered ventricular function is known to occur in brain pathologies. In the present study, we investigated anatomical and functional alterations to mouse ventricular cilia that result from mild TBI. We demonstrate that TBI causes a dramatic decrease in cilia. Further, using a particle tracking technique, we demonstrate that cerebrospinal fluid flow is diminished, thus potentially negatively affecting waste and nutrient exchange. Interestingly, injury-induced ventricular system pathology resolves completely by 30 days after injury as ependymal cell ciliogenesis restores cilia density to uninjured levels in the affected lateral ventricle.